2022
DOI: 10.1037/pag0000703
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of working memory items recoverable from long-term memory remains fixed despite adult aging.

Abstract: We explored whether long-term memory (LTM) retrieval is constrained by working memory (WM) limitations, in 80 younger and 80 older adults. Participants performed a WM task with images of unique everyday items, presented at varying set sizes. Subsequently, we tested participants’ LTM for items from the WM task and examined the ratio of LTM/WM retention. While older adults’ WM and LTM were generally poorer than that of younger adults, their LTM deficit was no greater than what was predicted from their WM perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 65 publications
4
35
0
Order By: Relevance
“…Effects of aging on working memory capacity have been widely documented (e.g., Cowan et al, 2006; Greene et al, 2020; Light & Anderson, 1985; Wingfield et al, 1988). Recent research has shown that older adults’ working memory capacity limitations can account for their deficits in long-term memory by constraining how much information becomes available in long-term memory (Forsberg et al, under review; but see Bartsch et al, 2019). Given that age-related working memory limitations appear to constrain long-term memory retention and that older adults are less likely to remember episodic associations at specific levels of representation in long-term memory (Greene & Naveh-Benjamin, 2020), it is important to assess whether older adults can initially remember specific details of associations in working memory.…”
Section: On the Relationship Between Working And Long-term Memorymentioning
confidence: 99%
“…Effects of aging on working memory capacity have been widely documented (e.g., Cowan et al, 2006; Greene et al, 2020; Light & Anderson, 1985; Wingfield et al, 1988). Recent research has shown that older adults’ working memory capacity limitations can account for their deficits in long-term memory by constraining how much information becomes available in long-term memory (Forsberg et al, under review; but see Bartsch et al, 2019). Given that age-related working memory limitations appear to constrain long-term memory retention and that older adults are less likely to remember episodic associations at specific levels of representation in long-term memory (Greene & Naveh-Benjamin, 2020), it is important to assess whether older adults can initially remember specific details of associations in working memory.…”
Section: On the Relationship Between Working And Long-term Memorymentioning
confidence: 99%
“…The authors found that although both short-and long-term memories were impaired in older adults compared to their young counterparts, the degree of impairment from STM to LTM was equivalent in both groups [42]. They interpreted their findings as supporting a shared encoding bottleneck between the two memory systems [42]. However, in this study, memories were not reproduced explicitly, allowing responses based on familiarity.…”
Section: Introductionmentioning
confidence: 63%
“…In both cases, participants' memories were assessed by showing them an object, which was either novel or an item from the memory array in 50% of trials and asking them to indicate their response by rating their confidence on a six-item scale. The authors found that although both short-and long-term memories were impaired in older adults compared to their young counterparts, the degree of impairment from STM to LTM was equivalent in both groups [42]. They interpreted their findings as supporting a shared encoding bottleneck between the two memory systems [42].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations